Microcirculatory response during on-pump versus off-pump coronary artery bypass graft surgery. (April 2016) - Bienz, Marc; Drullinsky, David; Stevens, Louis-Mathieu; Bracco, David; Noiseux, Nicolas
Objectives: The use of cardiopulmonary bypass (CPB) during coronary artery bypass graft surgery (CABG) is associated with a systemic inflammatory response, resulting in altered microcirculation. The aim of this study was to evaluate whether beating heart surgery can preserve the microcirculation. Methods: Sublingual microcirculation was characterized by a Sidestream Darkfield Imaging Microscope during off-pump (OPCABG) and on-pump (ONCABG) surgery. Microcirculatory parameters were evaluated during eight precise perioperative time points. Results: The quality of the microcirculation decreased during early ONCABG. OPCABG resulted in a significantly better microcirculation compared to ONCABG for three of six parameters during surgery. However, by the end of surgery and postoperatively, the microcirculatory parameters were no different between the groups. Conclusions: While the results do not show a marked preservation of the microcirculation during and after OPCABG compared to ONCABG, they coincide with the body temperature fluctuations of each group during and after surgery. Our work suggests that active warming could impact the microcirculation parameters.